Philosophy of Science as a Pillar of Rationality and Morality of Science - Muhammad Nurwahidin; Muhammad Kaulan Karima; Daniel Dwi Saputra; Veronika Windy Sulistiowati; Nofi Yani; Luthfia Nurlita; Jemi Adi Sastra; Herlina; Guspita Lando (Synergy: Journal of Collaborative Sciences, 2026)
The philosophy of science plays a fundamental role in establishing the framework of rationality and morality in scientific knowledge. This article aims to examine the philosophy of science as a reflective foundation that guides the development of science not only toward empirical truth but also toward ethical values and social responsibility. Using a literature review approach, this study analyzes the main concepts of the philosophy of science, including ontology, epistemology, and axiology, as well as their relevance in modern scientific practice. The findings indicate that scientific rationality cannot be separated from the philosophical framework that guides critical and systematic scientific thinking. Furthermore, the philosophy of science serves as a moral guardian of science, ensuring that the application of scientific knowledge remains aligned with humanitarian values and sustainability. This article contributes conceptually by emphasizing the integration of rationality and morality as a normative foundation for the development of science and scientific ethics in the modern era. Therefore, the philosophy of science stands as an essential pillar in maintaining the balance between scientific progress and moral values in human life.